2008
DOI: 10.1111/j.1741-3737.2008.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Patterns of Nonresident Fathers’ Involvement: The Role of Resources and Relations

Abstract: Using data from the Fragile Families and Child Wellbeing Study, we examined patterns of nonresident father involvement 1 and 3 years after a nonmarital birth (N = 893). Cluster analyses were used to determine patterns of involvement across different father behaviors. About half of fathers displayed low involvement when children were 1 and 3 years old, one fourth of fathers maintained high involvement, and equal remaining proportions increased or decreased involvement over time. Multinomial logistic analyses in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
102
5
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(117 citation statements)
references
References 35 publications
(51 reference statements)
8
102
5
2
Order By: Relevance
“…Ces facteurs sont d'ordre socio-démographique, tels le type d'union, la durée écoulée depuis la séparation du couple, l'âge des enfants, la trajectoire conjugale des parents, la distance entre les résidences Swiss et Le Bourdais, 2009). D'autres sont d'ordre social ou psycho-social : le niveau d'éducation des parents et le revenu des mères et des pères (Swiss et Le Bourdais, 2009) ; les conditions de garde des enfants établies au moment de la séparation, tant légales qu'informelles, la garde partagée, la perception du désir du partenaire de partager la garde, l'éva-luation des qualités parentales (Acoca, 2004 ;Beaudry et Parent, 1996), le degré de satisfaction des parents à l'égard des modalités de garde (Swiss et Le Bourdais, 2009) ; la qualité de la relation entre les parents séparés et les liens avec leurs familles d'origine (Ryan et al, 2008). Cependant, les statistiques concrètes qui identifient les familles occultent le fait que le parent non résidant conserve souvent des liens d'intensité variable avec ses enfants, en limitant la famille aux membres qui vivent sous le même toit.…”
Section: Contexte De La Recherche En Démographie De La Familleunclassified
“…Ces facteurs sont d'ordre socio-démographique, tels le type d'union, la durée écoulée depuis la séparation du couple, l'âge des enfants, la trajectoire conjugale des parents, la distance entre les résidences Swiss et Le Bourdais, 2009). D'autres sont d'ordre social ou psycho-social : le niveau d'éducation des parents et le revenu des mères et des pères (Swiss et Le Bourdais, 2009) ; les conditions de garde des enfants établies au moment de la séparation, tant légales qu'informelles, la garde partagée, la perception du désir du partenaire de partager la garde, l'éva-luation des qualités parentales (Acoca, 2004 ;Beaudry et Parent, 1996), le degré de satisfaction des parents à l'égard des modalités de garde (Swiss et Le Bourdais, 2009) ; la qualité de la relation entre les parents séparés et les liens avec leurs familles d'origine (Ryan et al, 2008). Cependant, les statistiques concrètes qui identifient les familles occultent le fait que le parent non résidant conserve souvent des liens d'intensité variable avec ses enfants, en limitant la famille aux membres qui vivent sous le même toit.…”
Section: Contexte De La Recherche En Démographie De La Familleunclassified
“…Ryan et al (2008) thus suggested that a father's engagement with children was associated with his relationships with his extended family members including his own parents and the mother's parents. Ryan et al (2008) found that the quality of relationships with extended family members was associated with changes in father engagement over time. More positive relationships that fathers have with their extended family members were associated positively with father engagement over time.…”
Section: Father Engagement and Extended Family Relationshipmentioning
confidence: 99%
“…Accordingly, a father's relationship with his parents influences his paternal engagement with children because of intergenerational learning in families (Johnson, 2001). Furthermore, Ryan, Kalil, and Ziol-Guest (2008) suggested that if fathers have positive relationships with the mothers' parents, grandparents may actively encourage the father to maintain strong engagement with their children based on the perspective of family systems theory. Ryan et al (2008) thus suggested that a father's engagement with children was associated with his relationships with his extended family members including his own parents and the mother's parents.…”
Section: Father Engagement and Extended Family Relationshipmentioning
confidence: 99%
See 2 more Smart Citations